Implementation Evaluation of Clinical Pathway in Aceh Mental Hospital with Poac Method - Saputra, Irwan; Rafsanjani, T.M.; Humaira, Humaira (Universitas Teuku Umar, 2022)
Rumah Sakit Jiwa Aceh (RSJ) is the only referral psychiatric hospital in Aceh Province. The most diagnosed disease in RSJ is Schizophrenia with an average length of stay in 2018 is 59.76 days. Schizophrenia is classified into severe mental illness due to its chronicity. The length of hospital stay is one indicator of the quality of mental health services. Other indicators are the effectiveness of services and the compliance of services with clinical pathways. Clinical pathway functions as a means of both cost and quality control of patient services. The purpose of this study is to evaluate the implementation of clinical pathway schizophrenia in Aceh Mental Hospital. This research uses qualitative methods. Primary data is collected by in-depth interviews. The study population was RSJ Management and Professional Care Providers (PPA) using a purposive sampling method. the implementation of clinical pathway schizophrenia was not optimal, this was due to the absence of a trial process, limited socialization, lack of PPA and management commitment, and the evaluation results not followed-up. The implementation of clinical pathway that is not optimal has an impact on the differences in services obtained between patients, increasing the length of stay (LOS) of schizophrenic patients and hospital losses. Therefore, Aceh's mental hospital needs to revise the clinical pathway of schizophrenia.